Transcriptional activation of the haem oxygenase-1 gene by cGMP via a cAMP response element/activator protein-1 element in primary cultures of rat hepatocytes. - Immenschuh, S (1998)
The expression of the rate-limiting enzyme of haem degradation, haem oxygenase-1 (HO-1), can be induced by various stimuli, including lipopolysaccharide, tumour necrosis factor alpha and NO. The NO signal can be transmitted by cGMP, therefore this study was aimed at testing the activation of the HO-1 gene by cGMP. In primary cultures of rat hepatocytes, both HO-1 mRNA and protein were induced by the NO donor sodium nitroprusside and 8-bromo-cGMP. The HO-1 mRNA induction by cGMP was prevented by the specific protein kinase G inhibitor KT5823. The cGMP-dependent HO-1 mRNA induction was dose-dependent and transcriptionally regulated, as determined by studies with actinomycin D and a nuclear run-on assay. Cycloheximide lowered the cGMP-dependent induction of HO-1 mRNA to about one half. Luciferase reporter constructs driven by about 800 bp of the 5'-flanking region of the rat HO-1 gene were transiently transfected into primary rat hepatocytes; 8-bromo-cGMP caused a 6-fold induction, which was obliterated by deletion and mutation of the cAMP response element/activator protein-1 (CRE/AP-1) (-665/-654) site. Thus HO-1 induction by cGMP appears to be stimulated by the protein kinase G pathway and may be mediated mainly via a CRE/AP-1 element in the rat HO-1 promoter.